2000
DOI: 10.1901/jaba.2000.33-271
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Intervention Implementation in General Education Following Consultation: A Comparison of Two Follow‐up Strategies

Abstract: This study examined two strategies for increasing the accuracy with which general education teachers implemented a peer tutoring intervention for reading comprehension. The intervention was implemented for 5 elementary school students who had been referred for consultation services. Initial implementation of the intervention by the teachers was variable, and the data exhibited a downward trend. When consultants held brief daily meetings with the teachers to discuss the intervention, implementation improved for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
292
5
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(324 citation statements)
references
References 17 publications
22
292
5
5
Order By: Relevance
“…Research has shown that high treatment integrity is associated with positive therapeutic outcomes (Fiske 2008;Noell et al 2002;Wilder et al 2006). Unfortunately, and despite receiving pre-service training, many practitioners do not maintain acceptable treatment integrity over time Noell et al 2000). With regard to clinical practice, it is not possible to properly evaluate the effectiveness of intervention plans if practitioners apply procedures inaccurately.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that high treatment integrity is associated with positive therapeutic outcomes (Fiske 2008;Noell et al 2002;Wilder et al 2006). Unfortunately, and despite receiving pre-service training, many practitioners do not maintain acceptable treatment integrity over time Noell et al 2000). With regard to clinical practice, it is not possible to properly evaluate the effectiveness of intervention plans if practitioners apply procedures inaccurately.…”
mentioning
confidence: 99%
“…Assessing treatment integrity entails direct observation of practitioners implementing procedures with the people in their care (Noell et al 2005;DiGennaro Reed and Codding 2011). Typically, observers use a recording form with steps that correspond to procedures that are listed on a written instructional or behavior support plan.…”
mentioning
confidence: 99%
“…In recent years, new programs have been developed to offer knowledge and experience to teachers, and different methods such as consulting to increase the effectiveness of these programs have been suggested (Mesa, Lewis-Palmer, & Reinke, 2005;Noell et al, 2000). One of these methods is performance feedback which can desirably change teacher behaviors and offer teachers opportunities to experience applying these newly learned methods in their classrooms (Scheeler, Ruhl, & McAfee, 2004).…”
mentioning
confidence: 99%
“…Performance feedback can be used in different educational settings (Codding, Feinberg, Dunn, & Pace, 2005;Noell et al, 2005) and for different purposes (Hagermoser-Sanetti, Luiselli, & Handler, 2007;Mortenson & Witt, 1998;Noell, Witt, Gilbertson, Ranier, & Freeland, 1997;Noell et al, 2000). Generally, PF can be used along with social rewards after teaching a new strategy to the teachers for use in their classrooms (Casey & McWilliam, 2008), or it can also involve problem solving or answering questions (Akalın, 2014a).…”
mentioning
confidence: 99%
“…According to Noell, Witt, Slider, Connell, Gatti and Williams (2005) many classrooms are not set up to accommodate the routines needed for interventions to be implemented adequately. Noell, et al (2005) investigated three levels of support: weekly interviews between the teacher and the consultant; interviews that focused on accurate step by step implementation of the intervention, and, performance feedback. They found that performance feedback produced higher treatment fidelity than the other two support conditions.…”
Section: Progress Monitoringmentioning
confidence: 99%